Práticas de gestão de pessoas voltadas ao servidor público com deficiência : uma análise da inclusão em órgão do Poder Judiciário - Sousa, Clarissa Gomes de (2024)
The objective of this study is to analyze people management practices within the Federal Justice of the 5th Region from the perspective of public servants with disabilities. To achieve this purpose, the following specific objectives were outlined: to describe the people management practices adopted by the Judiciary aimed at including public servants with disabilities; to identify the perceptions of public servants with disabilities regarding people management practices and the degree of inclusion; and to identify guidance practices aimed at the inclusion of people with disabilities in the Federal Judiciary. The theoretical constructs underpinning this investigation covered studies on people management in public service, people management and people with disabilities (PwD), and PwD in Public Administration. To achieve the research objectives, a basic qualitative, descriptive approach was used. The study was conducted with eighteen disabled employees, distributed across the judicial bodies of TRF-5, SJPB, SJPE, SJCE, SJRN, and SJSE, through interviews based on a semi structured script. The interviews were recorded, and their transcriptions enabled the distribution of statements into the following categories: recruitment and selection; placement and reception (the actual functional exercise); training and development; and performance evaluation. After categorization, the content analysis method was used. One of the key findings is that the inclusion of PwD in public service is not effective with the mere provision of reserved positions in public competitions. Instead, attention is required to their post-entry into the institution. Initially, it was noted that there is still inconsistency in setting the percentage of vacancies for PwD in public competition notices, suggesting the need for more uniformity by the JF5, based on the number of PwD already employed. It was also found that the existence of multiprofessional and interdisciplinary teams to assess PwD, following the biopsychosocial model, is not a reality, despite legal and normative requirements. Furthermore, it was evident that upon the arrival of employees with disabilities, little attention is paid to assessing their specific needs, in terms of providing accessibility resources and/or reasonable adaptations, starting from medical examination and extending through personnel departments to immediate supervisors. This has sometimes led to failures in the process of placement, reception, choice of work sectors, and assignment of tasks to employees with disabilities, as their limitations and barriers to functional exercise were not considered. It was also found that training efforts on the topic of PwD are still minimal and quite recent, with employees reporting various cases of attitudinal barriers related to stigma, stereotypes, and prejudice toward PwD, or simply due to ignorance. There is a need for the JF5 to institutionalize the offering of continuous training on this subject for all organizational actors, especially judges, directors, and manager-employees, as several cases were reported in which PwD felt they were seen as "unproductive" or "incapable," or even not welcomed when attempting to exercise their rights. Additionally, it was observed that the methodology for performance evaluation of PwD does not account for the specific conditions of employees with disabilities, leading them to be almost always evaluated in the same way as non-disabled people. Depending on the type of disability and specific limitations, this causes distortions and mistaken interpretations, especially when considering their productivity or lack thereof relative to the work assigned, particularly if there is no assessment of whether the work sector, assigned tasks, work format, completed hours, and required goals are suitable. Finally, it was observed how deeply rooted the issue of structural ableism is in society and, consequently, in the Judiciary, with difficulties for people with disabilities (PwD) to exercise their rights due to fear of being seen as "inferior." This highlights the need for institutional change capable of empowering PwD and providing organizational knowledge about accessibility and inclusion, to better welcome PwD into the workforce. The results presented aim to promote interaction with new research, managers, judges, and employees with and without disabilities, with the goal of making inclusion for PwD a reality in the public sector. Future research is suggested on how PwD perceive themselves when confronted with attitudinal barriers at work, especially regarding their ability to exercise their rights. It was noticed that there is often a tendency for PwD to hide their condition due to fear of judgment. New studies are also encouraged on people management practices for PwD in other judicial bodies, such as state courts and specialized justices, to allow for comparisons with the findings of this study.